Concentração nutricional em diferentes órgãos vegetais e fluorescência da clorofila a em Coffea canephora - Santos, Millena Monteiro dos (2021)
High productivity in coffee plantations has been achieved with the use of superior genotypes. For this, an adequate nutritional management is necessary, respecting the physiological specificities and nutritional demands of each cultivated material. The present study was divided into two chapters, in which the first aims to study the nutritional concentration of macro and micronutrients in different plant organs (leaf, flower, grain and straw) in nine genotypes of C. canephora, while the second aimed to whether to assess chlorophyll a fluorescence throughout the year at three times a day. Both experiments were carried out in the North of Espírito Santo, in a crop cultivated with nine genotypes comprising two Conilon coffee cultivars, in a randomized block experimental design, with three replications and three plants each plot. For the first chapter, leaf materials were collected every three months, from August 2019 to May 2020. Flowers were collected in the first flowering in July 2019 and fruits in June 2020, upon complete maturation. The materials were dried in an oven and sent for laboratory analysis to determine the nutritional content of macro and micronutrients. Data were subjected to analysis of variance followed by comparison of means and estimates of genetic parameters and grouping using the hierarchical method (UPGMA). Parameters linked to genetic improvement indicated that there is little influence of the environment on the nutritional concentration in plant tissues, flowers were the ones that presented the least environmental interference for the nutritional concentration. N, Fe and K were the macros and micronutrients found in higher concentrations in organs. For leaves, the concentrations of the main nutrients were high in the first seasons, decreasing in the last ones. For the second chapter, chlorophyll a fluorescence assessments were performed at two times of the year (summer and winter) and at three times of the day (morning: 07:00 h; noon: 12:00 h; afternoon: 17: 00 h), and leaf attribute evaluations. Cluster analyzes were performed using the UPGMA method and principal component analysis to identify correlations between ecophysiological parameters. Three groups of nine genotypes were formed according to the grouping method, with a cut in approximately 45%. Parameters of the JIP test showed trends of higher values for morning and noon (initial fluorescence), for afternoon only the quantum yield of the primary photochemistry. All reaction center (RC) variables showed similar behavior with trends towards higher values in the morning. In general, leaf attributes tended to be lower in winter and higher in summer in all groups. Group 1 formed by genotype 9 (NV2) presents greater dissimilarity when compared to the others. It was possible to observe through the multivariate analysis that the leaf attributes are correlated with the JIP parameters in relation to variability in seasons and times.